Financial Modeling of Health Maintenance Organizations - Coleman, John R. (1979)
The chronological development of computerized financial planning models for HMP development and operational planning are examined. The models are described in terms of their input, output, and degree of generalization and applicability to other HMO planning situations. The design, use, cost and impact of a generalized model on the HMO planning efforts of some planning groups are presented.